Recycled Paper Sludge (RPS) as Partially Replacement Material for Sand in Concrete - Lim, Albright; Ahmad Jeni, Muhammad Luthfi; Kosnin, Hilmi (Progress in Engineering Application and Technology, 2023)
Many research have been done recently on the use of waste materials in place of fine aggregates while making concrete. When compared to normal concrete, which could harm the environment if used excessively and is more expensive down the road, the usage of recycled paper sludge (RPS) in concrete will promote the idea of eco-friendliness and increase the strength of concrete. In this investigation, RPS substituted for up to 15% of the sand that is typically used as fine aggregate in concrete. The effectiveness of the RPS replacement concrete was compared to that of regular concrete after that. According to the findings, 5% RPS as sand replacement produces a slump height that is the closest to that of the control sample. Moreover, the highest water absorption was reached at the 15% RPS replacement ratio, or 4.773%. The distribution of RPS aggregates increased the voids, and the paper used in the concrete cubes had a high water absorption rate. Additionally, the closest concrete cube with a compressive strength of 25.03 MPa at age 28 days was made of 5% RPS concrete. As a result, the compressive strength dropped as the replacement RPS percentage increased. According to DOE mix design, a replacement percentage of 5% RPS is still acceptable, however RPS should not be replaced with sand more than 10%. Finally, the optimum content for this RPS research is 5% of percentages since it is still within the specified range based on the DOE concrete mix design 28 days.